Impact of DPP4 Inhibitors in Survival of Patients With Prostate, Pancreas, and Breast Cancer - Shah, Chintan; Hong, Young-Rock; Bishnoi, Rohit; Ali, Azka; Skelton, William Paul; Dang, Long H.; Huo, Jinhai; Dang, Nam H. (Frontiers in Oncology, 2020)
Background Dipeptidyl peptidase-4 (DPP4) is a cell surface protein expressed on different tissues and exhibits a crucial role in tumor biology as well as regulation of the immune system. We aim to study the impact of DPP4 inhibitors (DPP4i) in patients with prostate cancer (PRC), pancreatic cancer (PC) and breast cancer (BC). Methods Using the SEER and Medicare linked database, we identified patients with PRC or PC or BC with coexisting type II diabetes mellitus between 2007-2015. Patients were classified into four groups: (1) not on either DPP4i or metformin (reference group), this group included patients that were on anti-diabetic agents other than metformin or DPP4i (2) metformin only, (3) DPP4i only, and (4) DPP4i along with metformin (combination group). Overall survival (OS) analyses were performed using SAS®, version 9.4. Results We identified 15330 patients with PRC, 5359 patients with PC and 16085 patients with BC. In PRC cohort, patients on DPP4i had a significant survival advantage with HR 0.77 (95% CI: 0.64-0.93), P=0.005 when compared to the reference group. Patients taking metformin also had significant OS benefit with HR 0.87 (95% CI: 0.81-0.93), P<0.0001 when compared to the reference group. However, in BC cohort, OS did not favor the patients taking DPP4i with HR 1.07 (95% CI: 0.93-1.25, P=0.33). Similarly, in PC cohort, OS was indifferent for the patients on DPP4i with HR 1.07 (95% CI: 0.93-1.24, P=0.68). Upon subgroup analyses of PRC patients, the survival favored the group taking DPP4i, irrespective of the stage, use of chemotherapy, androgen-deprivation therapy, and prostatectomy or radiation therapy. Conclusions DPP4i seems to improve survival in PRC patients; however, not in PC or BC patients. While the exact mechanism involved remains to be elucidated, a prospective clinical trial would help to confirm these findings.